Economic aspects of a “middle layer” of administration and government: some experience from Austria - Walter Scherrer (Central European Public Administration Review, 2006)
There was no “middle layer” of government between the central state and the municipal level in the new member states of the European Union when these countries joined the EU recently. For various motivations – the ability to optimize access to EU funds being one of the motivations – the creation of a middle layer of regional government or administration has been discussed. In opposite to the new EU members Austria has already had a political system with three layers not only of administration but with three layers of government for several decades. Section 1 discusses major features of the territorial organization of Austria’s economy and its system of political decision making. Section 2 finds that history, a strong political preference for federalism, and pragmatism are major explanations for the emergence and durability of the system. Section 3 analyses the economic cost of Austria’s complex territorial organisation, and section 4 shows the scope for economic policy action at the state level using examples from the state of Salzburg.